Faktor Penentu Efisiensi: Diversifikasi Aset, Risiko, Ukuran Bank, dan Likuiditas - Annisa Alhadi; Muhammad Iqbal Fasa (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
Banking plays an important role in the economy both micro and macro. In addition, it is crucial for a country to have a strong and robust banking system. To realize a strong and robust banking banks need to maintain their efficiency. Therefore, it is necessary to identify the factors that affect efficiency, including asset diversification, risk, bank size and bank liquidity. The sample of this research are conventional banks with a total of 10 banks that have the largest share of assets in Indonesia. In this study to identify the effect of asset diversification, bank risk, bank size, and bank liquidity on bank efficiency used multiple linear regression analysis methods were used. This study concludes that asset diversification actually reduces bank efficiency. The increased bank risk, the better efficiency. Then, the size of the bank and liquidity have no effect on efficiency. Therefore, banks need to review the diversification strategy, ensure that the risks associated with each asset and portfolio as a whole are well-identified and look for opportunities to automate repetitive processes and reduce overall operational costs.